Soluble ST2 in coronary artery disease: Clinical biomarkers and treatment guidance - Zhang, Junyan; Chen, Zhongxiu; Ma, Min; He, Yong (Frontiers in Cardiovascular Medicine, 2022)
The IL-33/ST2 L signaling pathway is involved in the pathophysiological processes of several diseases and mainly exerts anti-inflammatory and antifibrotic effects. Soluble suppression of tumorigenicity 2 (sST2), which serves as a competitive inhibitory molecule of this pathway, is a member of the interleukin (IL)-1 family, a decoy receptor for IL33, thought to play a role in cardiac remodeling and the inflammatory process. However, the association between sST2 and coronary artery disease (CAD), one of the most common causes of heart failure, is still being explored. We therefore reviewed the research on sST2 in the field of CAD, including reflecting the atherosclerosis burden, predicting no-reflow, predicting prognosis, responding to myocardial remodeling, and guiding management, hoping to provide cardiologists with new perspectives.